Specification and charateristics manager in general hospitals Asurvey Study in Al-Rusafa Health Directorate Hospitals - الطائي علي حسون; ندة كريم بهار (Journal of Economics and Administrative Sciences, 2019)
Abstract This current study aims to know the characteristics of the doctors’ impact on success “doctors who work as managers specifically”. The sample contains from (60) doctors work in the three hospitals in Baghdad, The data collected with questionnaire, the main personnel characteristics the desire to work as hospitals managers. The study contains three chapters. The first is to the theoretical, background. The second is methodology and the third is the data analysis and also explains the results and conclusions and the recommendations. Specification and characteristics manager in general hospitals A survey Study in Al-Rusafa Health Directorate Hospitals